Deciphering Digital Emotions: A Comprehensive Sentiment Analysis on Social Media Data - Axele Bowen; Nia Adinda (Institute of Computer Science (IOCS), 2023)
In the ever-expanding digital landscape, understanding the nuances of human emotions as expressed on social media platforms is paramount. This research embarks on a comprehensive sentiment analysis journey, employing advanced Natural Language Processing (NLP) techniques to unravel the emotional tapestry within a carefully curated social media dataset. The study encompasses meticulous preprocessing steps, ranging from data cleaning to feature extraction, and culminates in model training using state-of-the-art architectures such as LSTM and BERT. The findings reveal intricate patterns and trends in sentiment dynamics, offering insights into emotional intensities, temporal fluctuations, and resonant themes. Comparative validations against existing literature and baseline models contribute to the robustness and contextualization of our approach. Ethical considerations, including privacy protection and bias mitigation, underscore the responsible foundation of our analysis. The research not only provides a granular understanding of digital sentiments but also paves the way for future advancements, addressing ongoing challenges and guiding stakeholders in navigating the evolving landscape of emotions within the digital realm.